Feasibility Analysis of Organic Rice Cultivation Business in Semarang City - Etty Soesilowati; Nana Kariada Tri Martuti; Dhita Prasisca Mutiatari (Muhammadiyah University Press, 2021)
This article describes how Benefit Cost (B/C) ratio, Return on Investment (ROI), Internal Rate Ratio (IRR), and Payback Period (PP) for organic rice cultivation in Semarang, Indonesia. The purpose of this study was to calculate the feasibility of organic rice cultivation and support the country’s food security in providing healthy food. The study used a quantitative approach with a sample size of 20 organic rice farmers in Semarang. The variables studied include the amount of immersed investment, cash flow, total costs required and net income in one planting period. The data were collected through observation techniques, questionnaires, and interviews. The results showed that 10 farmers suffered losses so that the business was not feasible to continue because the ROI IRR were at the level of -15% to -80%, PP was more than 1 year with the assumption of a reference interest rate of 3.5%. Meanwhile, the other 10 farmers have a decent business to continue because they get a profit of 6% to 168% per harvest with a maximum PP of 10 months. The biggest cost lies in the means of production, maintenance and product certification. The implication of this research is that the government should provide incentives or compensation for farmers who are just starting to practice organic cultivation and develop an integrated organic farming demonstration plot model so that it is possible for many people to learn how good organic farming practices are. This incentive can be supported by APBD funds or from other sources of funds, either in the form of venture funds, subsidies, exemption from certification fees, or livestock assistance.